ANALISIS LEARNING LOSS MAHASISWA SISTEM INFORMASI PADA MATA KULIAH ALJABAR LINEAR - Riana, Riana; Ibrahim, Malik; Sunardi, Sunardi (LPPM Universitas Bina Bangsa, 2024)
This study aims to analyze the phenomenon of learning loss experienced by Information Systems students in the Linear Algebra course, particularly in understanding the concept of Gauss-Jordan elimination during online lectures. A qualitative research method was employed with a sample of 59 third-semester students. A questionnaire was utilized as the research instrument for data collection. The findings revealed that 33% of the total respondents encountered significant difficulties in understanding the Gauss-Jordan elimination concept during online learning. These results indicate a significant impact of learning loss in the context of online education, which may affect students' understanding and academic performance. The implications of this research highlight the importance of efforts to enhance the effectiveness of online learning, including the development of more interactive and supportive teaching strategies, as well as improving the quality of interaction between instructors and students in the virtual environment. Further research is needed to gain a deeper understanding of the factors influencing learning loss and to develop more effective solutions for addressing the challenges of online learning in the future